MALAY OF KUALUH WORD ORDER IN LABUHANBATU UTARA: A STUDY OF SYNTACTIC TYPOLOGY - Pasaribu, Gumarpi Rahis; Mulyadi, Mulyadi (Premise: Journal of English Education and Applied Linguistics, 2024)
The word order in the Kualuh Malay language spoken in North Labuhanbatu is the subject of this research, which aims to investigate it. Study In this research, the qualitative research method was utilized.  Data for this study came primarily from interviews and participants' own experiences. The clauses or sentences that were discovered in the folklore served as the research's primary source of data. The studies of Miles and Huberman were utilized in order to make sense of the data. The process of assessing the research involved several stages, including data reduction, data display, and extracting conclusions from the data and verifying them. It is possible to draw the conclusion based on the findings of the research that the structure of the sentence patterns used in the Kualuh Malay language spoken in North Labuhanbatu contains VSO, SVO, OSV, VOS, OVS SV, VO, and OV. The word order pattern that should be followed in the declarative clause of a declarative sentence is SC, SVO, OVS. The word order pattern of the clause in this section is V-O and O-V, and it is vital that this pattern be followed. In an interrogative sentence, SV, SVO, VOS, and OSV can be used with nasal-affixed verbs or without them.